2009
DOI: 10.1007/s00477-009-0349-4
|View full text |Cite
|
Sign up to set email alerts
|

Encoding hydrologic information via a fractal geometric approach and its extensions

Abstract: We present the application of a deterministic fractal geometric approach-the so-called fractal-multifractal procedure, FMFP-to the modeling of hydrologic data at different resolutions. The FMFP can generate a wide range of complex patterns that are virtually indistinguishable from observed hydrologic data sets (e.g., rainfall series, radar images, clouds, contamination plumes, width functions). We illustrate the use of the FMFP for hydrologic data encoding and model simplification by comparing a few representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Since the last reason, the glance of rainfall modelling has changed fairly. Nowadays, there exists important efforts in the applications of derived multifractal models [1,7,14,19,21,23,24,26] and even more in multifractal random cascades models [ 5,6,8,9,15,16,17,30].…”
Section: Looking For a Model Of Rainfallmentioning
confidence: 99%
“…Since the last reason, the glance of rainfall modelling has changed fairly. Nowadays, there exists important efforts in the applications of derived multifractal models [1,7,14,19,21,23,24,26] and even more in multifractal random cascades models [ 5,6,8,9,15,16,17,30].…”
Section: Looking For a Model Of Rainfallmentioning
confidence: 99%
“…These measures are useful for describing the experimental observations, as reported by Frisch and Parisi (1985), Meneveau and Sreenivasan (1987), and Puthenveettil et al (2005). Multifractal is also used to characterize the wetland topography (Tchiguirinskaia et al 2000), airborne geophysical data (Tennekoon et al 2005), and to generate complex hydrologic spatiotemporal datasets (Cortis et al 2009(Cortis et al , 2010. For river networks, Seo et al (2014) examined the peak flow distribution on stochastic network models.…”
Section: Introductionmentioning
confidence: 97%
“…Inspired by the advent of chaos theory (e.g., Lorenz 1963) and by its usage to model precipitation (e.g., Rodriguez-Iturbe et al 1989), Puente and Obregón (1996), Puente et al (2001a, b), and Puente and Sivakumar (2007) showed that the FM method was able to capture hidden order in the dynamics of geophysical sets and demonstrated fruitful applications of such methodology for different rainfall sets gathered every few seconds (e.g., Puente and Obregón 1996;Cortis et al 2009Cortis et al , 2010Cortis et al , 2013Huang et al 2012). Indeed, the deterministic FM methodology may generate complex-looking sets with a relatively small number of parameters, and this happens despite the fact that the associated parameter-space is rather intricate, hence requiring a suitable optimization approach for a given set (Huang et al 2012.…”
Section: Introductionmentioning
confidence: 98%